Development of Islamic Education Evaluation System - Siti Kholidatur Rodiyah (STAI Miftahul Ula Nganjuk, 2018)
Education is essentially a change of knowledge, skills, attitudes and desirable behavior in students. Designing evaluation tools is one step that should not be left behind in learning planning and design. Through proper evaluation not only can determine the success of students achieving learning goals, but also at the same time can see the effectiveness of planned design programs.